ANALISIS BIBLIOMETRIK SHARING ECONOMY PUBLIKASI ILMIAH DI NEGARA-NEGARA SELURUH DUNIA - Tsuroyya putri saadah; M. Ruslianor Maika (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to determine the development map of scientific publications related to the "Sharing Economy". This research was conducted by collecting data through the Scopus database using the keyword "Sharing Economy". In this study, researchers used a quantitative descriptive method with bibliometric analysis. Based on the search results, researchers obtained 2,476 scientific work search documents which were then exported in BibTex format and processed using R-Packages software and Biblioshiny WebInterface, the results we found were that scientific publications containing the sharing economy have been carried out a lot as the years increase. This is of course very helpful as a reference for research literature on the sharing economy conducted in the future.